AKTIVITAS , TUGAS DAN FUNGSI DPRD DALAM PENENTUAN KINERJA DI KANTOR DPRD KABUPATEN MINAHASA UTARA - RACHMAN, ISMAIL (Sam Ratulangi University, 2014)
DPRD is institution that represents the society to implement the government plan. DPRD as the governmentinstitution has role to carry legislative function, budgeting function, and monitoring function. Legislativefunction is to make policy with Governor. Budgeting function is to organize and set the APBD which iscontains of budget for functional, task and job description for DPRD Provinsi. Monitoring Function is tomonitor the implementation of law government policy and governor’s decision.Keywords: Duty And Function of Regional House of Representatives DPRD, Performance